Religious Resilience of Hijrah Youth in the Midst of Modernization Flow: Challenges, Adaptation, and Consistency - Muhammad Adib Nuruzzaman; M. Yunus Abu Bakar (Fokus)
Modernization triggered an identity crisis that prompted the birth of a new social movement, the hijrah movement became a movement for identity search among millennials in Indonesia. This paper presents a complete explanation of the development of the hijrah movement in Indonesia and the efforts of hijrah youth to build religious resilience in the midst of modernization. With an analytical descriptive approach, this study collects data using a literature study, then analyzes it with thematic techniques. The goal is to provide actual insight into the impact of the hijrah movement and how hijrah youth adapt and maintain religious consistency. The results of this study show that the hijrah movement is a step to find the identity of the millennial generation who are experiencing an identity crisis in the midst of modernization. The challenges faced include conflicts between religious values and modern lifestyles, maintaining religious consistency in the digital era, to social stigma against the hijrah movement from various community groups. Efforts to build religious resilience among hijrah youth can be understood within the framework of the social construction theory of Peter L. Berger and Thomas Luckmann, which takes place through three dialectical stages: externalization, objectification, and internalization. The religious resilience built by the hijrah youth is not solely based on a dogmatic foundation, but is the result of complex social dynamics. Values such as staying away from dating, covering the aurat, and choosing to avoid usury transactions are not only understood as religious obligations, but also as a collective identity that gives direction and meaning in life.